Effectiveness of a formulation containing peptides and vitamin C in treating signs of facial ageing: three clinical studies. (22nd December 2020) - Escobar, S.; Valois, A.; Nielsen, M.; Closs, B.; Kerob, D.
Abstract: Objective: Vitamin C and peptides are widely used in cosmetic products but there is a paucity of clinical studies showing that the formulations are effective in treating signs of facial ageing. These 3 clinical studies evaluated the effectiveness of an anti‐ageing formula containing natural vitamin C (10%), biopeptides (rice and lupin), hyaluronic acid, and Vichy volcanic mineralising water, in amber glass ampoules with no preservatives (Peptide‐C ampoules). Methods: Dansyl chloride fluorescence labelling compared cell turnover for Peptide‐C ampoules vs untreated skin in 32 female subjects. Study 2, an open clinical study, evaluated the efficacy on wrinkles of Peptide‐C ampoules by investigator clinical scoring based on Dynamical Atlas visual assessment (N = 40) and subject self‐assessment questionnaires (N = 47). Study 3, an open clinical study, evaluated wrinkles by instrumental quantification with 3D fringe projection analysis (N = 40) and subject questionnaires (N = 51). Results: The mean cell turnover was faster for skin treated with Peptide‐C ampoules compared to untreated skin (17.1 days vs. 19.2 days; P < 0.0001). In study 2, after 28 days application of Peptide‐C ampoules, clinical grading of crow's‐feet wrinkles, forehead wrinkles and nasolabial folds decreased by 9%, 11% and 5%, respectively (all P < 0.05 vs baseline). Of 47 subjects, 77%, 64% and 79% indicated their skin seemed smoothed out, fine lines were less visible, and skin complexion was more radiant, respectively. In study 3, the number of wrinkles decreased by 11.5% after 29 days application of Peptide‐C ampoules vs baseline ( P < 0.05) and 65% of subjects responded the fine lines were less visible. Conclusion: This formulation of a combination of anti‐ageing ingredients in ampoules, allowing a minimalist formula, showed significant results on improving facial wrinkles and radiance. Abstract : A formulation containing peptides and vitamin C, in innovative packaging allowing a minimalist formula, demonstrated effectiveness and high subject satisfaction for wrinkle reduction and skin rejuvenation. Résumé: Objectif: La vitamine C et les peptides sont régulièrement utilisés dans les produits dermocosmétiques mais il existe peu d'études cliniques sur l'efficacité des formulations sur les signes du vieillissement cutané du visage. Trois études cliniques ont évalué l'efficacité d'une formule anti‐âge contenant de la vitamine C naturelle (10%), des biopeptides (riz et lupin), de l'acide hyaluronique et de l'eau minéralisante volcanique de Vichy, dans un format d'ampoules en verre ambré, sans conservateur (ampoules Peptide‐C). Méthodes: Une première étude a comparé par la technique de chlorure de Dansyl le renouvellement cellulaire avec la formulation ampoules Peptide‐C et la peau non traitée chez 32 sujets féminins. La seconde étude, en ouvert, a évalué l'efficacité clinique sur les rides des ampoules Peptide‐C en se reposant sur les Atlas Dynamiques (N=40) et les questionnaires d'auto‐évaluation des sujets (N=47). La troisième étude, ouverte, a évalué les rides par quantification instrumentale avec l'analyse de projection de franges 3D (N=40) et les questionnaires d'autoévaluation des sujets (N=51). Résultats: Le renouvellement cellulaire était plus rapide pour la peau traitée avec des ampoules de Peptide‐C comparées à la peau non traitée (17.1 jours contre 19.2 jours ; p<.0001). Dans l'étude 2, après 28 jours d'application des ampoules Peptide‐C, l'évaluation clinique des rides de la patte d'oie, du front et des plis naso‐labiaux a montré une amélioration de 9 %, 11 % et 5 %, respectivement (tous p<0, 05 vs baseline). Sur 47 sujets, 77%, 64% et 79% ont indiqué que leur peau semblait respectivement lissée, que les ridules étaient moins visibles et que le teint de la peau était plus radieux. Dans l'étude 3, le nombre de rides a diminué de 11, 5 % après 29 jours d'application des ampoules Peptide‐C par rapport à la baseline (p<0, 05) et 65 % des sujets ont répondu que les ridules étaient moins visibles. Conclusion: Cette combinaison d'ingrédients anti‐âge dans un format d'ampoules, et une formulation minimaliste, a montré des résultats significatifs sur l'amélioration des rides faciales et de l'éclat du teint